Dc leakage behavior and conduction mechanism in (BiFeO3)m(SrTiO3)m superlattices - Ranjith, R. (2011)
Leakage current behavior of (BiFeO3)m(SrTiO3)m superlattice structures was studied and analyzed at different temperatures (303–473 K) in the light of various models. While bulk limited Poole–Frenkel emission was observed to dominate the leakage current in the temperature range of 303–383 K, the space charge limited conduction was observed up to 473 K. With a Poole–Frenkel emission type of conduction, the activation energy range of -0.06–0.25 eV was calculated. The physical parameters, calculated from the analysis, correlate with the intrinsic properties. Such analysis of leakage current facilitates interface engineering of heterostructures for device applications.